2016
DOI: 10.1016/j.polymdegradstab.2016.06.025
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic environmental degradation of glass reinforced polymer composites

Abstract: Synergistic effects involved in the environmental degradation of Glass Reinforced Polymer (GRP) composites were examined in this research. Six GRPs based on E-glass and ECR-glass fibers with four different polymer resins were exposed either individually or in combination to ultraviolet (UV) radiation, water condensation and elevated temperature for approximately 1000 hours. The composites were monitored for weight changes as a function of time and their surfaces were examined after the tests using optical and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
25
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 24 publications
6
25
0
1
Order By: Relevance
“…This phenomenon was caused by either the polymer becoming excessively brittle because of increased crosslinking, or by the formation of micro‐cracking due to chain scission resulting from photo‐oxidation reactions induced by UV irradiation. Similar phenomena have been observed previously . Figure E shows that the erosion was not as significant for sample A.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…This phenomenon was caused by either the polymer becoming excessively brittle because of increased crosslinking, or by the formation of micro‐cracking due to chain scission resulting from photo‐oxidation reactions induced by UV irradiation. Similar phenomena have been observed previously . Figure E shows that the erosion was not as significant for sample A.…”
Section: Resultssupporting
confidence: 89%
“…Similar phenomena have been observed previously. 20 Figure 2E shows that the erosion was not as significant for sample A. Thus it was concluded that sample A was more UV-stable or that UV radiation was unable to penetrate through the entire glass fabric, confirming the results of the YI analysis.…”
Section: Optical Changes In Glass Fibre Reinforcementssupporting
confidence: 68%
“…This phenomenon could potentially be chalking of the polymer, and the tiny particles might be the photodegradation products of carbon fiber/epoxy microdroplet composite as a result of the photo‐oxidation induced crosslinking or chain scission from the UV radiation. Lu et al reported the formation of tiny particles in their study of glass fiber‐reinforced polymer composites under synergistic environmental conditions, and particles larger (20 μm) than those observed in our sample were observed, owing to greater UV irradiation intensity. Furthermore, upon increasing the exposure time of the microdroplet composite surface to 300, 560, 800, and 940 hours, respectively, the tiny particles became bigger and greater in number than those in the 40 hours aging sample (Figure 5C‐F).…”
Section: Resultsmentioning
confidence: 40%
“…The erosion of material properties due to UV irradiation and the degradation mechanism of epoxy and its composites has been investigated, and it has been suggested that the short‐term exposure to UV causes changes in surface morphology alone, such as discoloration, chalking, micro‐cracking, and pitting and flaking of composites . Furthermore, the discoloration observed was attributed to the formation of a quinone methide structure .…”
Section: Introductionmentioning
confidence: 99%
“…Деструкция поверхности ПКМ при совместном воздействии УФ-облучения и термовлажностных режимов оказывается интенсивнее, чем при их последовательном действии (синергизм). Это доказано при исследовании потерь массы серии СП в работе [56]. Убедительным примером ускорения деструкции полимерных матриц в открытых климатических условиях является наложение термоциклов, имитирующих условия эксплуатации авиационной техники (режим «взлет -посадка») на конструктивно подобные эле-менты и образцы свидетели из СП и УП [10].…”
Section: таблицаunclassified